Ongoing Exogenous Crises and Economic Policy Countermeasures: Peculiar Case of Serbian Tourism - Malovic, Marko; Mihajlović, Milan Đ; Muhi, Bela (Poslovna ekonomija, 2023)
In this paper we argue that in spite of the grave economic, political and health consequences of the ongoing exogenous crises (COVID-19 cum economic downturn stemming from Russian-Ukranian conflict), before too long Serbian tourism exhibited something similar to the V-shaped recovery (and then some) by means of a) government subsidies, b) substituting domestic for (temporarily) absent foreign tourists and by c) soaring prices of tourist services at stable exchange rate which more than compensate the industry for the reflation comeback.